PKM METODE PENYUSUNAN PERATURAN DESA DI DESA SUNSEA KECAMATAN NAIBENU KABUPATEN TIMOR TENGAH UTARA - Stefanus Don Rade; Mary Grace Megumi Maran; Yohanes Leonardus Ngompat (LPPM Institut Pendidikan Nusantara Global, 2025)
Village Regulations play an important role in regulating the lives of village communities so that they are more directed, fair, and in accordance with local needs. However, many village governments still experience obstacles in its preparation, especially in terms of legal procedures and community participation. This community service activity was carried out in Sunsea Village with the aim of providing training and technical assistance to village officials, BPD, and community leaders regarding methods of drafting Village Regulations in accordance with laws and regulations. Activities were carried out through a participatory approach with lecture methods, group discussions, and simulations of drafting Perdes. The results of the activity showed an increase in participants' understanding of the formal and technical procedures for drafting Perdes. This activity is expected to improve the quality of village legal products in Sunsea Village.